Pengembangan Badan Usaha Milik Desa (BUMDes): Pilihan Strategi Pemberdayaan di Provinsi Lampung - Abbas, Safwa Salsabila; Atika, Dewie Brima; Apandi (Wacana Publik, 2024)
Village-Owned Enterprises (BUMDes) are Village business institutions managed by the community and the Village government in an effort to strengthen the Village economy and are formed based on the needs and potential of the Village. The Lampung Provincial Government, especially the Dinas PMDT of Lampung Province is a regional apparatus that has the authority to assist the central government in encouraging village economic development and growth through BUMDes. This study aims to analyze the strategy implementation process by Dinas PMDT of Lampung Province in developing BUMDes and to identify what are the inhibiting factors from implementing strategy implementation by Dinas PMDT of Lampung Province in developing BUMDes. This research is a qualitative descriptive study that was studied using 3 indicators of strategy implementation according to Hunger & Wheelen (2003), namely programs, budgets, and procedures. The results of this study indicate that the implementation of strategies in the development of BUMDes by Dinas PMDT of Lampung Province namely by running the E Samdes Program with its activities namely Bimtek and Coaching Clinic, but the program does not have budget transparency and does not have a clearly structured program implementation procedure. The inhibiting factors for implementing this strategy in the development of BUMDes are internal factors, namely the absence of technical guidelines for codifying BUMDes and the lack of competence in human resources.